Information Literacy Skills and Academic Discipline as Predictors of Electronic Resources Use by Science Undergraduates in Public Universities on Osun State Nigeria - Adenariwo, Kehinde Fausat; Oketunji, Ibidapo (Communicate: Journal of Library and Information Science, 2023)
The study investigated information literacy skills and academic discipline as predictors of electronic resources use by science undergraduates in public Universities on Osun State, Nigeria. The study adopted survey research design and the population of the study consisted of 1,827 pure science students in two public universities in Osun State, Nigeria. A Two-stage, (purposive and proportional) was used to select a sample size of 182. A structured questionnaire was used and the Data were analysed using descriptive and findings revealed that Information literacy skills (β=0.495, p < 0.05) had positive and significant prediction on e-resources use by pure science undergraduates of public universities in Osun State, Nigeria. Additionally, academic discipline (β=0.063, p > 0.05) had no significant influence on e-resources use by pure science undergraduates of public universities. Information literacy skills and academic discipline jointly predicted e-resources use by pure science undergraduates of public universities in Osun State, Nigeria (F (2,126) = 29.467, p < 0.05). Since information literacy skills and academic discipline significantly predicted e-resources use by pure science undergraduates of public universities in Osun State, Nigeria, the study recommend that there is a need to educate the undergraduates of public universities on information literacy as this will help improve their level of information literacy skills making them explore the use of e-resources optimally towards enhancing their academic pursuit.